Analysis of the Practice of Captive Marriage in the Perspective of Feminism - Jacob, Ananias Riyoan Philip; Muskanan, Frans Wilmat; Saragi, Ofwa Wati (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study wants to explain the injustice of women's rights in the habit/practice of capture marriage in Waimangura Village, West Wewewa District, Southwest Sumba Regency. This study also wants to identify whether women's helplessness in the practice of capture marriage is their choice or because of power pressure The purpose of this study is to find out how the existence of women in the practice of capture marriage. This research uses Simonne De Beauvoir’s existentialist feminisms theory This research uses a qualitative approach with a descriptive approach, while the data collection technique uses interview techniques, the subjects in this study consist of Waimangura Village women, Waimangura Village Government, PERUATI community and traditional leaders. The methods used are the interview method, and the documentation method. Based on the results of this study existentialist feminism, influenced by the thought of Simone de Beauvoir, has a keen view of the practice of capture marriage "Wenda Mawine". This view is based on ideas about freedom, autonomy, and dignity of individuals, especially women. Women's Backwardness Existentialist feminism sees the practice of capture marriage as a form of oppression against women that hinders their ability to reach their full potential. This can result in underdevelopment in women's lives, both personally and professionally.